ANALISIS KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK KELAS X SMKN 1 JEMBER MELALUI MODEL PROJECT BASED LEARNING - H, Fachrum Fairus Nurlaila; Ani, Hety Mustika; Tiara, Tiara (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
The ability to think creatively is a fundamental aspect in achieving excellent learning outcomes aligned with curriculum goals. Students' creativity is crucial for optimizing the attainment of the Merdeka Curriculum Learning Objectives Criteria. This study aims to analyze creative thinking abilities through the Project Based Learning (PjBL) model. The research location was selected using purposive area sampling method and conducted at SMK Negeri 1 Jember, specifically in the 10th grade of Digital Business Department for the Basic Principles of Marketing subject, focusing on the Learning Achievements of Marketing Goods and Services in the Academic Year 2023/2024. The study population comprised all 10th grade Digital Business students, with the sample selected from Digital Business 1 class. This quantitative research employed a descriptive approach with a Pre-Experimental Design of the One Shot-Case Study type. Results from creative thinking ability tests indicated that students achieved 80% (creative) in project tasks and 79% (creative) in essay tasks. Findings demonstrate that the PjBL model can effectively measure and analyze students' creative thinking abilities.